ANALISA RANCANGAN BAND REJECTION FILTER UNTUK WIMAX FREKUENSI 3.5 GHz - Oktaviani Sari, Linna; Safrianti, Ery; Hidayat, Fauzi (SAINSTEK, 2016)
The development of technology-based 4G Broadband Wireless Access (BWA) is growing rapidly. In the BWA network is required high-speed connection and large capacity to access the internet compared to previous 3.5G technology. One of technology in the 4G BWA grown today is WiMAX IEEE 802.16d standard. WiMAX IEEE 802.16d standard is using the 3.5 GHz frequency. In this frequency, WiMAX have problems to be applied in Indonesia. This is due to the satellite in Indonesia use the same frequency with the WiMAX frequencies. For the implemention in Indonesia, it is necessary to design a band rejection filter to avoid interference between Imax and satellite. This research has been analyzed and designed Band rejection filter using the software Advanced Design System (ADS) 2011.01. The Responses are used in this design is Chebyshev response, because the Chebyshev response can produce a high degree of steepness. The results showed that the design of band rejection filter can refuse satellite frequency at a frequency of 3.5 GHz in the range of 30-50 dB with bandwitdh 120 MHz.